Progression of ulcerative colitis following diversion colitis - Katsuki, Yaguchi; Yusuke, Matsune; Reiko, Kunisaki; Kentaro, Araki; Hideaki, Kimura; Yoshiaki, Inayama; Jiro, Kumagai; Shin, Maeda (Clinical Journal of Gastroenterology, 2022)
Diversion colitis and ulcerative colitis (UC) can be caused by different mechanisms; however, several case reports have described the development of typical UC following diversion colitis. A 63-year-old man underwent Hartmann’s operation following a diagnosis of perforation of a sigmoid colon diverticulum and peritonitis. Stoma closure was performed 4 months later, and the portion of the sigmoid colon with the diverticulum was unintentionally left as a blind end. Following stoma closure, hematochezia worsened, and he was diagnosed as having developed diversion colitis only in the blind sigmoid colon. Intermittent use of topical mesalazine enemas controlled the bowel symptoms; however, 4 years after the stoma closure, bloody stools were observed again. Colonoscopy revealed coarse and friable granular mucosa with adherent mucopurulent exudate in the rectum, and mucosal erythematous edema with adherent mucopurulent exudate in the blind sigmoid colon. The histological findings indicated basal plasmacytosis, and goblet cell depletion and cryptitis in the lamina propria, which is characteristic of UC. To the best of our knowledge, this is the fourth description of a patient who developed UC following diversion colitis. Local inflammation may have triggered the development of UC through hematogenous or lymphogenous circulation of lymphocytes or autoantibodies.